2006
DOI: 10.1089/neu.2006.23.496
|View full text |Cite
|
Sign up to set email alerts
|

Bioengineered Strategies for Spinal Cord Repair

Abstract: This article reviews bioengineered strategies for spinal cord repair using tissue engineered scaffolds and drug delivery systems. The pathophysiology of spinal cord injury (SCI) is multifactorial and multiphasic, and therefore, it is likely that effective treatments will require combinations of strategies such as neuroprotection to counteract secondary injury, provision of scaffolds to replace lost tissue, and methods to enhance axonal regrowth, synaptic plasticity, and inhibition of astrocytosis. Biomaterials… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
124
0
3

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 184 publications
(128 citation statements)
references
References 116 publications
1
124
0
3
Order By: Relevance
“…'Combinatorial' neural tissue engineering strategies have been suggested to be essential to promote various aspects of neural regeneration (such as nerve fiber regeneration, suppression of scar formation and immune responses, promotion of blood vessel growth) within the complex, multi-faceted pathology of SCI [36][37][38][39][40]. Such synergistic approaches have the potential to regenerate the injured spinal cord with varying degrees of efficacy, but none have been successfully translated into the clinic [41].…”
Section: Discussionmentioning
confidence: 99%
“…'Combinatorial' neural tissue engineering strategies have been suggested to be essential to promote various aspects of neural regeneration (such as nerve fiber regeneration, suppression of scar formation and immune responses, promotion of blood vessel growth) within the complex, multi-faceted pathology of SCI [36][37][38][39][40]. Such synergistic approaches have the potential to regenerate the injured spinal cord with varying degrees of efficacy, but none have been successfully translated into the clinic [41].…”
Section: Discussionmentioning
confidence: 99%
“…A variety of materials of natural and synthetic origin, have been previously shown to promote adhesion, proliferation, neurite extension, and neuronal differentiation of neural cells in vitro and in vivo [26][27][28]. Synthetic polymer-based biomaterial scaffolds have the added advantage of controlled chemistries and mechanical properties [29,30], while enabling display or release of neurotrophic factors [31,32].…”
Section: Introductionmentioning
confidence: 99%
“…Synthetic polymer-based biomaterial scaffolds have the added advantage of controlled chemistries and mechanical properties [29,30], while enabling display or release of neurotrophic factors [31,32]. Of the various scaffold configurations proposed to date [27,28,30], electrospun polymer substrates have exhibited excellent neurogenic properties, due to their high surface area and porosity, and fibrous ECM-like geometries [33,34].…”
Section: Introductionmentioning
confidence: 99%
“…The pathophysiology of spinal cord injury is a highly complex process that involves primary and second-ary injuries, and the underlying mechanisms have not been definitively established [5][6][7] . Therapeutic interventions to treat SCI remain limited, and various strategies have been tested in animal models [8][9][10] . Previous studies have shown that transplantation of several different types of precursor/stem cells promoted axonal regeneration and functional recovery in animal models of SCI [11][12][13][14][15][16] .…”
Section: Introductionmentioning
confidence: 99%
“…Tissue engineering with biomaterial scaffolds has brought novel possibilities for the treatment of spinal cord injury [9,16] . Several types of synthetic biodegradable polymers have been tested, including poly (glycolic acid) (PGA), poly (L-lactic acid) (PLLA), poly (Δ-caprolactone) (PCL) and poly (lactic-coglycolic acid) (PLGA).…”
Section: Introductionmentioning
confidence: 99%